3T proton MR spectroscopy evaluation of spinal cord lesions - Sathyanathan, Babu Peter; Raju, Bharathi Priya; Natarajan, Kailasanathan; Ranganathan, Ravi (Indian Journal of Radiology and Imaging, 2018)
Objective: The objective of this study was to evaluate intramedullary spinal cord lesions using magnetic resonance spectroscopy and correlate the results with histo-pathological examination (HPE). Materials and Methods: Approval for this study was obtained from our institute ethical committee. Overall, 50 patients were recruited (29 male and 21 female), with a maximum age of 53 years and minimum age of 7 years. The mean age group of the study was 33 years. Standard magnetic resonance imaging (MRI) spine was done on a Siemens Skyra 3Tesla MRI scanner. MR Spectroscopy (MRS) was performed for all patients with intramedullary spinal lesions after getting written consent. It was performed using single-voxel method. The change in the metabolite peak was observed in each case and the results were compared with HPE. These collected data were analyzed using SPSS 16.0 version. Descriptive statistics, frequency analysis, and percentage analysis were used for categorical variables; and for continuous variables, mean and standard deviation were analyzed. McNemar's test was used to find the significance between conventional MRI MRS. In the above statistical tool, the probability value 0.05 is considered as significant level. Results: From our study, we observed that by applying routine MRI sequences alone, we could only detect around 58% of the cases correctly. However, when MRS was done along with the conventional MR imaging, the number of cases detected significantly increased to 84%. By applying McNemar's test and comparing the conventional MRI and MRS with HPE, it was found that statistically significant difference exists with P value of 0.007. Conclusion: MRS of the spinal cord is a promising tool for research and diagnosis because it can provide additional information complementary to other non-invasive imaging methods. It is an emerging tool and adds new biomarker information for characterization of spinal cord tumors, to differentiate benign from malignant lesions and to prevent unnecessary biopsies and surgeries.
Keywords: Spinal cord tumors; spinal MR spectroscopy; 3 Tesla